Feminist Discussions on The Remembrance of Earth’s Past Trilogy - Aiqing Wang (Humanus: Jurnal Ilmiah Ilmu-ilmu Humaniora, 2021)
As the first Asian Hugo Award laureate, Liu Cixin is an illustrious science-fiction writer in China, whose chef-d’oeuvre is an award-winning trilogy entitled Remembrance of Earth’s Past, or more widely renowned by the title of its first volume, viz. The Three-Body Problem. The series not only features intercivilisational belligerence via a fecundity of imagination and richness of imagery-evoking representation, but also manifests humanity and benevolence, so it has attained a loyal readership and commercial success. Notwithstanding critical acclamation, this male-authored trilogy encounters contentiousness concerning gender discrimination. I propound that the Remembrance of Earth’s Past series does not exhibit sexism, though there are depictions with gender stereotypes.